NHC-stabilized Al(III) and Ga(III) cationic alkyls: Synthesis, structure and use in hydrosilylation catalysis. (15th January 2021) - Bolley, Anaëlle; Specklin, David; Dagorne, Samuel
Graphical abstract: Low-coordinate Al(III) and Ga(III) alkyl cations stabilized by N -heterocyclic carbene ligands were characterized as strong Lewis acidic species and successfully exploited as selective as alkyne, benzaldehyde and CO2 hydrosilylation catalysts. Highlights: Low-coordinate carbene-stabilized Al(III) and Ga(III) alkyl cations are characterized. They stand as strong Lewis acids as estimated from the Gutmann-Beckett method. They mediate the trans -hydrosilylation of various alkynes. Carbonyl substrates could also be catalytically reduced using such cationic electrophiles. Abstract: Cationic Al(III) and Ga(III) species supported by N -heterocyclic carbene (NHC) ligands, (IDipp)AlMe2 (PhBr)] + ([1 ] +, IDipp = 1, 3-bis(2, 6-diisopropylphenyl)imidazolin-2-ylidene) and (IDipp)GaMe2 ] + ([2 ] + ), were prepared and structurally characterized as B(C6 F5 )4 − salts via ionization of the corresponding neutral precursors (IDipp)MMe3 (M = Al, Ga) with [Ph3 C][B(C6 F5 )4 ] in PhBr at room temperature. Both [1 ][B(C6 F5 )4 ] and [2 ][B(C6 F5 )4 ] salt were isolated in high yield and their solid state structures established through X-ray crystallographic studies. Cations [1 ] + and [2 ] +, which are rare examples of structurally characterized tris-organyl Al(III) and Ga(III) cations, stand as potent Lewis acids as experimentally estimated through the Gutmann-Beckett method. These cations were further exploited in hydrosilylation catalysis of alkynes, benzaldehyde and CO2 using HSiEt3 as an hydrosilane source. Hydrosilylation of 1-hexyne, 4-phenylbutyne and phenylacetylene led to the formation of the corresponding Z-selective products 3 –5, respectively, while benzaldehyde was converted to PhCH2 OSiEt3 (6 ). Cations [1 ] + and [2 ] + also slowly catalyze CO2 hydrosilylation with the selective formation of the methanol-equivalent MeOSiEt3 .